Inhibitory Activity of HEp-2 Cells by Honey from Indonesia - La Ode Sumarlin; Anna Muawanah; Farhan Riza Afandi; Adawiah Adawiah (Jurnal Kimia Sains dan Aplikasi, 2019)
Indonesian local honey contains active compounds that have the potential as an antioxidant and anticancer, primarily as a laryngeal anticancer through the inhibition of HEp-2 cells. This study aims to determine the anticancer activity of several types of honey in Indonesia through the inhibition of HEp-2 cells. Samples used in the form of Trigona, Longan, Rambutan, and Kaliandra honey obtained from honey farmers in Sulawesi and Java, Indonesia. Honey samples extracted by using methanol, then liquids partition was carried out consecutively using n-hexane and ethyl acetate. The cytotoxicity test for HEp-2 cells was carried out using the MTT method (3- (4,5-dimethyl thiazol-2-il) -2,5-diphenyl tetrazolium bromide). The results showed that all honey samples were active against preventing HEp-2 cells with the highest inhibition activity from longan honey with ethyl acetate extract at 65.18% at 100 ppm. Longan honey has decreased HEp-2 cell inhibitory activity after fractionation. Indonesian local honey, namely trigona honey, kaliandra honey, rambutan honey, and longan honey, can be used as a supplementary supplement for patients with laryngeal cancer.